Effectiveness of maintenance approaches for High Reliability Organizations. Issue 3 (2015) - Andriulo, Serena; Arleo, Maria Antonietta; de Carlo, Filippo; Gnoni, Maria Grazia; Tucci, Mario
Abstract: In recent years companies are paying more attention on Business Continuity Management. BCM focuses both on potential threats identification and on management of unexpected block process. These two aspects are the basis of High Reliability Organization. The HRO paradigm was developed several years ago in high-risk organizations. It integrates two relevant approaches: preventing unexpected events and resilient organizations. The aim of this study is to define a rough but effective approach to support HROs in evaluating their most "compliant" maintenance approaches. The main phases of the study are: the identification of the main HRO features (both prevention and resilient ones), the identification of the main maintenance approaches used to date and finally the evaluation of their compliance according to HRO features. The paper presents a new method to evaluate the different maintenance approaches: in addition to productivity, it's also considered the necessity to guarantee production continuity following unpredictable events.